Аналіз факторів впливу на споживання електроенергії при запровадженні «Концепції «зеленого» енергетичного переходу України до 2050 року» - Sudarykov, Alexander (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
On the way to EU membership, Ukraine joined the "European Green Deal", which aims to achieve zero greenhouse gas emissions and zero environmental pollution by transitioning from the use of fossil fuels to renewable sources of energy and raw materials in the member states of the European Union by 2050. The concept of the "green" energy transition of Ukraine by 2050 was formulated, which involves a change in approaches to the development of energy with an emphasis on the problem of combating climate change and sustainable economic development. When achieving the goals of the "green" transition, it is important to understand which factors have the greatest impact on electricity consumption. It is promising to include such factors in electricity demand forecasting models. These models will become increasingly important to ensure network reliability and efficiency. Identifying the factors that affect energy consumption can drive innovation in energy-efficient technologies and practices. The article concludes that electricity consumption in Ukraine is affected by the same main factors as in other countries of the world. The desired reduction in electricity consumption can be achieved both by purely economic measures (increasing tariffs) and by more acceptable, technological measures. However, in the conditions of war, there are additional difficulties, such as the difficulty of forecasting the structure, state, and development of the energy system on the energy market. A significant part of the population now has more urgent problems than energy conservation, so the role of the state in this issue is increasing. Ukraine's energy system has already suffered significant destruction, and this process is ongoing and may continue for an indefinite period of time. Despite the difficulties, the lost power system equipment is gradually being replaced with new, more technologically advanced equipment. Some of the enterprises that had significant consumption were either lost or failed. The most adapted to new problems turned out to be the trade sector and the service sector and part of the population. Here, there is a rapid transition to the use of own generators, solar panels and electric transport, which reduces the consumption of electricity from the state power system. Industry, taking into account the funds required for this, will replace technologies with more energy-efficient ones after the end of the active phase of the war.